2009
DOI: 10.1111/j.1365-2567.2008.03015.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell receptor binding affinities and kinetics: impact on T‐cell activity and specificity

Abstract: SummaryThe interaction between the T-cell receptor (TCR) and its peptide-major histocompatibility complex (pepMHC) ligand plays a critical role in determining the activity and specificity of the T cell. The binding properties associated with these interactions have now been studied in many systems, providing a framework for a mechanistic understanding of the initial events that govern T-cell function. There have been various other reviews that have described the structural and biochemical features of TCR : pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
336
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 317 publications
(343 citation statements)
references
References 108 publications
(191 reference statements)
4
336
1
2
Order By: Relevance
“…Previous studies (16,41) indicate that the contribution of CD8 to TCR/pMHC interaction is dependent on ligand C B A affinity. However, it is unknown whether the properties of TCRs can determine the magnitude of CD8 contribution (29). It has been demonstrated that CD8 engages in the TCR/pMHC interaction in the second stage after the TCR/pMHC complex is formed (41).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies (16,41) indicate that the contribution of CD8 to TCR/pMHC interaction is dependent on ligand C B A affinity. However, it is unknown whether the properties of TCRs can determine the magnitude of CD8 contribution (29). It has been demonstrated that CD8 engages in the TCR/pMHC interaction in the second stage after the TCR/pMHC complex is formed (41).…”
Section: Discussionmentioning
confidence: 99%
“…The affinities of the TCRs, as measured the by surface plasmon resonance (SPR) ( Table 1 and Fig. S1), span the entire affinity range of naturally selected TCRs (K D , ∼1-100 μM) (29) and thus provide a suitable system for studying the correlation between TCR affinity and functional activities. To investigate the antitumor activities of the TCRs, we characterized them in primary splenocytes isolated from A2-K b transgenic mice (38), a model for studying HLA-A2-restricted TCRs (35,39).…”
Section: Panel Of Gp209-specific Tcrs Shows Different Avidity and Funmentioning
confidence: 99%
See 3 more Smart Citations